Intertemporal Choice and Income Regularity: Non-Fungibility in a Lab-in-the-Field Experiment - Berber Kramer; David Kunst (Tinbergen Institute, 2018)
This paper tests whether the choice of when to be paid depends on the income type. A lab-in-the-field experiment in Kenya asked dairy cooperative members to allocate both an irregular windfall and their regular milk payments between two dates. Participants allocated the windfall to the earlier of the two dates, in line with theory, but allocated milk payments to the later date. Survey evidence suggests that allocations of regular dairy income were significantly more patient because farmers earmarked milk payments, but not the irregular windfall, for bulky expenditures. Given that compliance with informal contracts depends on whether the timing of payment aligns with recipient preferences, these findings have implications for contract design in rural value chains.
Keywords: D03; Q13; O12; 330; time preferences; mental accounting; fungibility; collective marketing